Monitoring of Togeanensis Babirusa (Babyrousa togeanensis) Population in Togean Islands National Park - Yusuf, Yusuf; Rosyid, Abdul; Korja, I Nengah; Muhasinin; Hamsi, Muh Suyuti; Moh Ramadan (Universitas PGRI Palembang, 2024)
Babyrousa togeanensis is an endemic wildlife of Sulawesi Island, Indonesia. Government development programs and the increased activities of local communities in the Togean Islands National Park area are causing this animal habitat to be narrowed. Monitoring the Babyrousa togeanensis population is crucial to updating their numbers in protected areas to avoid extinction. This study used direct and indirect observation methods to investigate the Babirusa population at Urulepe Point, Togean Island. Our study showed that the total population of Babirusa individuals in the study coverage area was 58 individuals per km2, higher than the number reported in the previous year. The increase in the number of Babirusa populations can be assumed to have occurred due to increased awareness of local people about the importance of protected wildlife, as well as a piece of evidence that conservation by the government through the TNKT has been successfully implemented. Environmental conditions in TNKT are good enough to support the habitat and needs of life and breeding of Togean Babirusa. The most effective method of monitoring Babirusa was camera traps because the wildlife avoids humans, making the direct transect strip method less effective for encountering Babirusa.